2011
DOI: 10.1603/ec11004
|View full text |Cite
|
Sign up to set email alerts
|

No Fitness Cost for Wheat's <I>H</I> Gene-Mediated Resistance to Hessian Fly (Diptera: Cecidomyiidae)

Abstract: Resistance (R) genes have a proven record for protecting plants against biotic stress. A problem is parasite adaptation via Avirulence (Avr) mutations, which allows the parasite to colonize the R gene plant. Scientists hope to make R genes more durable by stacking them in a single cultivar. However, stacking assumes that R gene-mediated resistance has no fitness cost for the plant. We tested this assumption for wheat's resistance to Hessian fly, Mayetiola destructor (Say) (Diptera: Cecidomyiidae). Our study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 83 publications
0
22
1
Order By: Relevance
“…An insect feeding in a susceptible plant, however, grows normally and changes in gene expression proceed according to a development regulatory regime. During an incompatible interaction, plants resume normal growth after some initial growth deficit following the Hessian fly attack [33]. Biochemically, nutrient and energy metabolism is temporarily suppressed, whereas various plant defense pathways are activated, including the strengthening of cell walls and elevation of toxic chemicals such as reactive oxygen species, protease inhibitors, lectins, and secondary metabolites [14,15,16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…An insect feeding in a susceptible plant, however, grows normally and changes in gene expression proceed according to a development regulatory regime. During an incompatible interaction, plants resume normal growth after some initial growth deficit following the Hessian fly attack [33]. Biochemically, nutrient and energy metabolism is temporarily suppressed, whereas various plant defense pathways are activated, including the strengthening of cell walls and elevation of toxic chemicals such as reactive oxygen species, protease inhibitors, lectins, and secondary metabolites [14,15,16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in Arabidopsis , transgenic lines containing the R gene RPM1 exhibited a 9% reduction in seed production relative to susceptible controls [ 23 ]. However, some studies have shown costs of individual R genes that are lower or effectively zero [ 16 , 24 ]. It therefore appears that R genes may vary in their costs, with some being substantial and others non-existent [ 17 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The defense response includes feeding deterrent lectins (Subramanyam et al, 2008), fortification of the leaf surface (Kosma et al, 2010), production of reactive oxygen species (Liu et al, 2010), and other mechanisms (Liu et al, 2007). This resistance is very efficient, killing larvae in 3 to 5 d, but plants carrying a Hessian fly-resistance gene have no yield penalty regardless of whether the plants are infested (Anderson et al, 2011).…”
mentioning
confidence: 99%